2018
DOI: 10.1093/cercor/bhy260
|View full text |Cite
|
Sign up to set email alerts
|

Sparse Representation in Awake Auditory Cortex: Cell-type Dependence, Synaptic Mechanisms, Developmental Emergence, and Modulation

Abstract: Sparse representation is considered an important coding strategy for cortical processing in various sensory modalities. It remains unclear how cortical sparseness arises and is being regulated. Here, unbiased recordings from primary auditory cortex of awake adult mice revealed salient sparseness in layer (L)2/3, with a majority of excitatory neurons exhibiting no increased spiking in response to each of sound types tested. Sparse representation was not observed in parvalbumin (PV) inhibitory neurons. The nonre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 78 publications
7
33
1
Order By: Relevance
“…The microheterogeneity was similar for GABAergic and glutamatergic neurons. Our results thus differ from auditory cortex, where response patterns are different and local microheterogeneity is much smaller for (parvalbumin-positive) GABAergic neurons than for glutamatergic neurons (Maor et al, 2016; Liang et al, 2018; Liu et al, 2019). We conclude that despite the shared input and firing behavior during development (Babola et al, 2018), functional heterogeneity dominates within bands in the dorsal IC of adult mice.…”
Section: Discussioncontrasting
confidence: 96%
“…The microheterogeneity was similar for GABAergic and glutamatergic neurons. Our results thus differ from auditory cortex, where response patterns are different and local microheterogeneity is much smaller for (parvalbumin-positive) GABAergic neurons than for glutamatergic neurons (Maor et al, 2016; Liang et al, 2018; Liu et al, 2019). We conclude that despite the shared input and firing behavior during development (Babola et al, 2018), functional heterogeneity dominates within bands in the dorsal IC of adult mice.…”
Section: Discussioncontrasting
confidence: 96%
“…The precision of tonotopic organization at the cellular level has recently become a controversial issue (34)(35)(36)(37)(38)(39), based mostly on studies from mice. Although a tonotopic map of monkey A1 at the cellular level has not been reported, previous studies using extracellular electrophysiological recording of neuronal activities have suggested that the tonotopic preference of cortical cells within local regions of A1 is homogeneous, consistent with a smooth tonotopic organization.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that A1 responses sparsify with development and that auditory experience early in life can shape this process (Liang et al, 2019; Meng et al, 2019). We here show that visual experience later in life has a similar capability.…”
Section: Discussionmentioning
confidence: 99%